Technology Acceptance Model and Learning Management Systems: Systematic Literature Review - Cavus, Nadire; Omonayajo, Babatomiwa; Mutizwa, Melissa Rutendo (International Journal of Interactive Mobile Technologies (iJIM), 2022)
As the Internet has evolved rapidly, Learning Management Systems in recent years, particularly during the pandemic era, have become increasingly popular and can effectively override time and gives people new insights into the education field. A substantial amount of research was performed on a Technology Acceptance Model (TAM) framework and popularity in Learning Management Systems, in general, was indicated. However, there are gaps in established awareness of representative academic literature that form the basis of research in LMS and TAM. The summary of the current research effort on TAM implementation in the area of LMS is the main objective of this systematic literature review. This systematic literature review found 21 related studies between 2010 and 2020 based on the aim of this research through the systematic search of the most popular scientific databases. We hope that the findings of the review will inspire institutional administrators and users to recognize the factors that influence the quality and effectiveness of the use of LMS by TAM.